2008
DOI: 10.1002/dmrr.798
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic education of diabetic patients

Abstract: Therapeutic patient education is a patient-centred approach, focussed on patients' needs, resources, values and strategies. It allows patients to improve their knowledge and skills not only concerning their illness but also their treatment. It brings a better quality of life, a greater therapeutic compliance and a reduction in complications. The most difficult part of therapeutic patient education occurs when patients must change their behaviour. Motivational interviewing and cognitive-behavioural approaches c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 8 publications
0
33
1
9
Order By: Relevance
“…The inaccuracy and deficiency in knowledge may be due to lack of specific and comprehensive education, as indicated by the patients, and poor understanding related to low literacy levels. Although knowledge by itself does not necessarily lead to improved self-care behaviours or outcomes (Norris et al 2001), an understanding of the disease, its course and treatment and how all these interact are pre-requisites for effective selfcare (Golay et al 2008;Persell et al 2004). Some studies have also demonstrated a positive relationship between disease knowledge and self-care behaviours (Van den Arend et al 2001;Persell et al 2004) and glycaemic control (Colleran, Starr & Burge 2003;Persell et al 2004).…”
Section: Knowledge About Diabetes and Its Treatmentmentioning
confidence: 99%
“…The inaccuracy and deficiency in knowledge may be due to lack of specific and comprehensive education, as indicated by the patients, and poor understanding related to low literacy levels. Although knowledge by itself does not necessarily lead to improved self-care behaviours or outcomes (Norris et al 2001), an understanding of the disease, its course and treatment and how all these interact are pre-requisites for effective selfcare (Golay et al 2008;Persell et al 2004). Some studies have also demonstrated a positive relationship between disease knowledge and self-care behaviours (Van den Arend et al 2001;Persell et al 2004) and glycaemic control (Colleran, Starr & Burge 2003;Persell et al 2004).…”
Section: Knowledge About Diabetes and Its Treatmentmentioning
confidence: 99%
“…Apesar de já existirem evidências de que a educação de pacientes diabéticos e seus parentes constitui um ponto fundamental tanto para encorajar rastreamentos mais regulares para RD quanto na prevenção e tratamento da RD (14,(19)(20)(21)(22)(23) , a maioria dos pacientes na nossa amostra relata que nunca havia recebido alguma informação ou palestra sobre diabetes de algum profissional de saúde, bem como não haviam recebido algum tipo de material informativo sobre DM. Uma grande parte da nossa amostra também nunca havia participado de programas de educação sobre DM.…”
Section: Discussionunclassified
“…Elle les a visionnées une première fois dans une visée exploratoire, à la recherche de critères lui permettant de construire la grille d'analyse des entretiens. Les grilles utilisées ont été validées et utilisées en éducation thérapeutique 18 2). La péda-gogue a visionné une deuxième fois tous les entretiens (12) et les a analysés avec cette nouvelle grille comprenant des items bio-psycho-sociaux, avec un accent particulier sur la recherche des ressources du patient.…”
Section: Elaboration De L'outil D'évaluationunclassified
“…Elle est centrée notamment sur les besoins, les connaissances et les compétences du patient, mais également sur ses ressources 2 . L'éducation thérapeutique du patient est appliquée pour des malades chroniques ; elle élargit l'approche biomédicale habituellement enseignée dans nos facultés par une approche systé-mique et psychosociale.…”
Section: Introductionunclassified